Collection Management in Senior Secondary School Libraries—An Analytical Study - Das, Debabrata; Mahapatra, R. K.; Panigrahi, Suraj (JOURNAL OF INDIAN EDUCATION, 2014)
The article states the status of the CBSE affiliated senior secondary school libraries and brings out the history and system of school libraries in Bhubaneswar, Odisha. It mentions the support and contribution of government and non- government organisation for the development of the CBSE affiliated school libraries. It also highlights the salient features of CBSE affiliated school libraries of Bhubaneswar. It also reflects on activities of school librarians for the development of school libraries in Bhubaneswar city.